Building pathways out of poverty in Baidoa: Evidence from a randomized controlled trial at endline - Leight, Jessica; Karachiwalla, Naureen; Hirvonen, Kalle; Rakshit, Deboleena (International Food Policy Research Institute, 2024)
Somalia is one of the poorest countries in the world, and severe poverty, ongoing armed conflict, and recurring droughts and floods have created a humanitarian crisis characterized by a high level of inter nal displacement. Baidoa city—the site of this evaluation—hosts 517 sites for internally displaced per sons (IDP), with almost 600,000 households, and 64 percent of the individuals living in these sites are women and girls. According to the second Somali High Frequency Survey (Pape and Karamba 2019), IDP settlements (along with rural areas) face a particularly high level of poverty, exacerbated by high unemployment rates and the absence of income-generating opportunities.